2017
DOI: 10.3390/pharmacy5040067
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students’ Knowledge and Attitude toward Registration Trials and Clinical Research: A Survey in a Japanese University Hospital

Abstract: Clinical research plays a fundamental role in establishing new treatments. Clinical research coordinators are considered essential in clinical research, and medical professionals such as pharmacists often take on this role. Pharmacy students can be considered future candidates for this task. We used questionnaires to survey the knowledge of and attitudes toward registration trials and clinical research of pharmacy students at Tokushima University Hospital. All pharmacy students (103) to whom questionnaires wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The knowledge of pharmacy students about specific research misconduct terminologies was found to be comparable with a previous investigation of pharmacy students in a Japanese University Hospital [7]. Current and previous results indicate that scientific misconduct represents a significant issue that needs to be addressed [7]. In the current study, almost less than half of responders were aware of research misconduct terminologies such as plagiarism, fabrication, and falsification.…”
Section: Discussionsupporting
confidence: 85%
“…The knowledge of pharmacy students about specific research misconduct terminologies was found to be comparable with a previous investigation of pharmacy students in a Japanese University Hospital [7]. Current and previous results indicate that scientific misconduct represents a significant issue that needs to be addressed [7]. In the current study, almost less than half of responders were aware of research misconduct terminologies such as plagiarism, fabrication, and falsification.…”
Section: Discussionsupporting
confidence: 85%
“…In our previous survey of 597 nurses, 26% of the respondents expressed their willingness to work as CRCs [ 29 ]. In another survey of pharmacy students, we found that more than 90% were aware of the CRC role and 29% and 41% were willing to carry out and coordinate research, respectively [ 30 ]. Exposure on and education of the broader role of CRCs to nurses, pharmacists and their students may lead to establish a suitable clinical research team in the future.…”
Section: Discussionmentioning
confidence: 99%